The Influence of Motivation, Organizational Culture, and Work Environment on Employee Performance Through Job Satisfaction as a Mediating Variable (Human Resource Management Literature Review) - John E.H.J., FoEh; Sinaga, Jhonni (Dinasti International Journal of Economics, Finance & Accounting, 2025)
Previous studies are very important in scientific writing. Previous or related studies play a role in strengthening the hypothesis and explaining the correlation or influence between variables. This article examines the impact of motivation, organizational culture, and work environment on employee performance, with job satisfaction as a mediating variable, based on a survey of human resource management literature. This article intends to propose a hypothesis regarding the influence between variables for further research. The findings of this study show that: 1) motivation substantially positively influences job satisfaction; 2) organizational culture has a substantial positive influence on job satisfaction; 3) the work environment substantially positively influences job satisfaction; 4) motivation substantially positively influences employee performance; 5) organizational culture has a substantial positive influence on employee performance; 6) the work environment substantially positively influences employee performance; and 7) job satisfaction has a substantial positive effect on employee performance.